Perinatal Outcomes Associated With Obstructive Sleep Apnea in Obese Pregnant Women - Louis, Judette (2012)
OBJECTIVE: To investigate the associations between obstructive sleep apnea (OSA) and maternal and neonatal morbidities in a cohort of obese gravid women. METHODS: Participants were enrolled in a prospective observational study designed to screen for OSA and describe the possible risk factors for and outcomes of OSA among obese (BMI 30 kg/m(2) or higher) pregnant women. Women underwent an overnight sleep study using a portable home monitor. Studies were manually scored by a central masked Sleep Reading Center using American Academy of Sleep Medicine diagnostic criteria. An apnea hypopnea index of 5 or greater was considered diagnostic of OSA. Perinatal outcomes were compared between women with and without OSA. RESULTS: Among 175 women, OSA prevalence was 15.4% (13 mild, 9 moderate, 5 severe). Compared with no-OSA (AHI<5), the OSA group had a higher BMI (46.8 ±12.2 vs. 38.1± 7.5 kg/m(2), p=0.002) and more chronic hypertension (55.6 vs. 32.4%, p=0.02). Maternal complications included: maternal death (n=1, amniotic fluid embolus [no-OSA group]) and cardiac arrest (n=1, intraoperative at cesarean delivery [OSA group]). One previable birth and two stillbirths occurred in the no-OSA group. Among live births, OSA was associated with more frequent cesarean delivery (65.4 vs. 32.8%, p=0.003), preeclampsia (42.3 vs. 16.9, p=0.005), and NICU admission (46.1 vs. 17.8, p=0.002). After controlling for BMI, maternal age, and diabetes, OSA (OR 3.55 [1.1–11.3]), prior preeclampsia (OR 2.79 [1.09–7.19]), and hypertension (4.25 [1.67–10.77]) were associated with developing preeclampsia. CONCLUSION: OSA among obese pregnant women is associated with more frequent preeclampsia, neonatal intensive care unit admissions, and cesarean delivery.